Pengembangan Media Pembelajaran Barang Bekas Komponen Elektronika Berbantuan Simulator Livewire untuk Meningkatkan Kreativitas Mahasiswa pada Materi Elektronika Dasar - Miftah Miftah; Nurasyah Dewi Napitupulu; Muhammad Zaky; Ketut Alit Adi Untara (Postgraduate, University of Mataram, 2024)
The purpose of this research is to develop learning media for passive electronic components assisted by Livewire simulator to increase student creativity in basic electronics material. This research was conducted in the Physics Education Study Program, Faculty of Teacher Training and Education, Tadulako University. Development research time for 8 months. The subjects of this research are physics education students who program basic electronics courses. The measured change is the validation value of learning media development from expert respondents and students. To increase student creativity is measured through a creativity questionnaire. This research is a type of research and development or known as Research and Development (R&D). This research uses several stages of research: (1) Potential and problems; (2) Data collection; (3) Product design; (4) Design validation; (5) Design revision; (6) Product trial; (7) Product revision; (8) Usage trial; (9) Product revision; and (10) Mass production. From the results of the study, the N-gain value of the pretest and posttest data was 0.47 or N-gain in the medium category. Therefore, it can be concluded that the development of used electronic component media can increase student creativity on the subject of basic electronics